Legal Protection for Sexual Violence Victims via Amendments to the (EIT) Law - Elisabeth S. Telussa; Retsky Timisela; Della P. Ajawaila (CV. Era Digital Nusantara, 2026)
This research analyzes legal protections for digital sexual violence victims in Indonesia following the second amendment of the Electronic Information and Transactions (EIT) Law and the Sexual Violence Crimes Law. Utilizing a juridical-normative approach, the study examines the harmonization between these statutes to mitigate victim recriminalization risks. Findings indicate that while Law 1/2024 refines defamation norms, practical enforcement often lacks gender sensitivity, frequently misapplying EIT provisions over specialized victim rights. Consequently, the research advocates for a victim-centered paradigm shift through two primary mechanisms: the imposition of additional sanctions specifically revoking digital access for perpetrators and the establishment of a Digital Victim Trust Fund based on restorative justice principles. Ultimately, effective protection necessitates synchronized regulations and proactive content moderation by digital platforms. Such reforms ensure that Indonesia’s criminal justice system prioritizes individual human dignity and comprehensive recovery for survivors within the rapidly evolving global digital communication ecosystem by integrating technological and legal mechanisms.